2016
DOI: 10.1007/s10096-016-2682-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vancomycin versus nafcillin in enhancing killing of methicillin-susceptible Staphylococcus aureus causing bacteremia by human cathelicidin LL-37

Abstract: Recent studies have demonstrated that anti-staphylococcal beta-lactam antibiotics, like nafcillin, render methicillin-resistant Staphylococcus aureus (MRSA) more susceptible to killing by innate host defense peptides (HDPs), such as cathelicidin LL-37. We compared the effects of growth in 1/4 minimum inhibitory concentration (MIC) of nafcillin or vancomycin on LL-37 killing of 92 methicillin-susceptible S. aureus (MSSA) isolates. For three randomly selected strains among these, we examined the effects of nafci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This complexity may be one unrecognized pharmacodynamic faculty helping to explain the differences in clinical efficacy of different antibiotic classes irrespective of MIC in standard AST testing. For example, vancomycin is a far inferior agent to beta-lactams clinically against S. aureus , despite showing potent activity in vitro [ 25 , 26 ]. These effects may unfortunately contribute to the poorer outcomes of patient who are denied beta-lactam drugs due to penicillin “allergies” listed in their medical records [ 27 ].…”
Section: Bactericidal Vs Bacteriostatic In the Context Of Innate Immumentioning
confidence: 99%
“…This complexity may be one unrecognized pharmacodynamic faculty helping to explain the differences in clinical efficacy of different antibiotic classes irrespective of MIC in standard AST testing. For example, vancomycin is a far inferior agent to beta-lactams clinically against S. aureus , despite showing potent activity in vitro [ 25 , 26 ]. These effects may unfortunately contribute to the poorer outcomes of patient who are denied beta-lactam drugs due to penicillin “allergies” listed in their medical records [ 27 ].…”
Section: Bactericidal Vs Bacteriostatic In the Context Of Innate Immumentioning
confidence: 99%
“…This reduced pathogenesis is dependent upon interactions with the antibacterial host response in the lung. This finding bolsters the concept that antibiotics can sensitize resistant organisms to the host immune response, which has been demonstrated for host-derived antimicrobial peptides [18,19]. Based upon these findings, it is likely that current laboratory-based testing underestimates the in vivo efficacy of existing antibiotics to combat multidrug-resistant pathogens.…”
Section: Plos Pathogensmentioning
confidence: 57%
“…In contrast, antibiotics can cooperate with innate immune effectors to enhance bacterial killing. Exposure to cell wall-active antibiotics enhances MRSA killing by the host-derived antimicrobial peptide, LL-37, and LL-37 killing of Salmonella enterica is enhanced upon exposure to multiple classes of antibiotics [18,19]. Further, A. baumannii has been found to alter…”
Section: Introductionmentioning
confidence: 99%
“…While combinations with antibiotics comprise a great quantity of the research, combinations with other antimicrobial agents are also described in this review. Nafcillin MSSA CIs [191] Enterococcus faecium Ceftaroline DAP-susceptible parent strain, R6370, 8019 [192] Ampicillin DAP-susceptible parent strain, 8019; AMPand VAN-resistant isolate [192,193] Ertapenem DAP-susceptible parent strain, R6370, 8019 [192] Oritavancin VAN-resistant CI [194] Oritavancin + Ampicillin…”
Section: Synergymentioning
confidence: 99%
“…Furthermore, many studies have proposed that the ability of an antimicrobial agent to synergize with LL-37 depends on whether it is a bactericidal or a bacteriostatic substance. It has been suggested that synergism results when bactericidal agents are paired together, or when bacteriostatic agents are paired; the combination of bacteriostatic and bactericidal substances will lead to an antagonistic interaction [177,191]. Leszczyńska et al also suggest that the synergistic effects between LL-37 and the bactericidal substance are enhanced if the antibiotic targets the bacterial wall structure.…”
Section: Combinations With Ll-37mentioning
confidence: 99%